The Effect of Holding Time Variations in MgB2 Superconductor with Addition Nickel Prepared by Powder in Sealed Tube Method - Hendrik (Talenta Publisher, 2020)
In this research, the effect holding time on the synthesis of MgB2 superconducting material with the addition of nickel has been carried out using the powder in sealed tube method. MgB2 is a superconductor which has a critical temperature of 39 K. The addition of 0%, 4%, and 8% Ni was added to study its effect on the superconductivity characteristics of MgB2. The sample preparation process begins by weighing the raw materials in the form of Mg, B and Ni powders according to stoichiometric calculations. The material is then crushed for 1 hour using mortar agate then put into a stainless steel tube SS 316L and the PIST pressing process is carried out with a pressure of 5 MPa, then the sintering process is carried out using a muffle furnace with a temperature of 800ÂºC and holding time for sintering temperature for 1 hour, 3 hours and 5 hours. Samples were characterized by means of XRD, SEM-EDS and Cryogenic Magnet. The results of phase identification through XRD showed that the phases formed were MgB2, MgNi2.5B2, MgO, Mg and Ni. Morphological structure and elemental composition were seen through SEM-EDS. From the Cryogenic Magnet test, pure MgB2 samples with a holding time of 1 hour had a critical temperature Tc of 36.29 K and did not have Tc. Meanwhile, pure MgB2 at a holding time of 5 hours has a Tc of 42.18 K and a Tc of 25.55K.